Analysis of Injuries in Competitive Equestrian Events - Haines, Carver; Jensen, Hanna K; Karim, Saleema A; McGhee, Linda (Clinical journal of sport medicine, 2022)
Current equestrian sport-related acute injury research is sparse. The goal of this study is to explore equestrian injury types stratified by population and equestrian discipline. Injury reports from the US Equestrian Federation (USEF) were compiled from 2015 through 2019, and the prevalence of different injury types within the main equestrian disciplines was calculated. Retrospective cohort study from USEF accident report data. Athletes competing at USEF sanctioned equestrian events. Equestrian participant's age group, sex, and equestrian event type are the independent variables. Frequency of types of injuries in equestrian events stratified by equestrian discipline, age (junior vs senior), and sex. Three thousand four hundred thirty equestrian athletes injured from 441 816 total athlete exposures during 2015 to 2019 were analyzed showing an injury rate between 0.06% and 1.18% for each discipline with an overall injury rate of 780 per 100 000 athlete exposures. Hunter-jumper and 3-day eventing had the highest injury rates. Head injuries and bone injuries were the most common types. No clinically significant differences in injury rates were observed between males and females or junior and senior equestrian athletes. Equestrian sports have an overall injury rate of 780 per 100 000 athlete exposures in the certified competition setting. Hunter-jumper and 3-day eventing have an increased injury rate compared with nonjumping disciplines. These data should help equestrian event clinicians to anticipate the types of injuries and help outpatient clinicians make preparticipation medical eligibility and assist in counseling for equestrian sports.